Analysis of User Satisfaction on Master Alumni of Islamic Education Management (MPI) at IAIN Kudus - Efferi, Adri (Pascasarjana IAIN Kudus, 2023)
This research is based on field conditions; there is a gap between the knowledge gained from lectures and the working conditions faced, so users feel dissatisfied. Even though alumni work in the community or the world of work, it indirectly becomes a free promotion for the study program. It will certainly be an attraction for prospective students. This study aims to determine the user satisfaction level of IAIN Kudus Postgraduate alumni, especially from the Islamic Education Management (MPI) Study Program. This research uses a qualitative approach and surveys as tools for data collection. Analysis techniques use the flow of exposure, reduction and conclusion. The research results are that the competencies obtained by alums are quite relevant to enter the world of work; the high level of user satisfaction with alumni evidenced this.Analisis Kepuasan Pengguna Alumni Magister Manajemen Pendidikan Islam di IAIN Kudus. Penelitian ini berdasarkan kondisi lapangan, terdapat kesenjangan antara ilmu yang diperoleh dari perkuliahan dengan kondisi kerja yang dihadapi, sehingga pengguna merasa tidak puas. Padahal kiprah alumni di masyarakat atau dunia kerja, secara tidak langsung menjadi promosi gratis bagi program studi, dan tentunya akan menjadi daya tarik bagi calon mahasiswa. Tujuan penelitian ini mengetahui tingkat kepuasan pengguna alumni Pascasarjana IAIN Kudus khususnya dari Program Studi Manajemen Pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif, dan survei sebagai alat untuk pengumpulan data. Teknik analisis menggunakan alur pemaparan, reduksi dan penarikan kesimpulan. Hasil dari penelitian, kompetensi yang diperoleh alumni cukup relevan untuk memasuki dunia kerja, hal ini dibuktikan dengan tingkat kepuasan pengguna yang tinggi terhadap para alumni.